Analisis Penerapan Trading Strategy dan Investment Strategy Terhadap Saham yang Tergabung Dalam Indeks LQ 45 - Wilson, Timothy; Kurniasari, Florentina (Universitas Multimedia Nusantara, 2018)
ABSTRACT The aim of this research is to determine the performance of Trading and Investment Strategy in buying and selling decisions for shares listed in the LQ45 index consistently for period of January 1st 2015 – December 31st, 2017. There are 32 companies selected as sample using purposive sampling method. The research using secondary data which had taken from the stock price in opening and closing market. As a quantitive descriptive research, this research is also analyzed the stock that reached highest and lowest price in the market during that period. The result of this research shows that Investment strategy is the best strategy to produce higher return than Trading strategy, in which UNVR is the best performer. Keywords: Stock Return, Technical Indicator, Investment, Trading, MACD